Some biochemical, blood gases and haematological alterations in downer cow - Hasan Güzelbekteş; Alparslan Coşkun; Aliye Sağkan Öztürk; İsmail Şen; Mahmut Ok (Eurasian Journal of Veterinary Sciences)
The aim of this study is to determine some biochemical, blood gases and haematological alteration in downer cows . Nine recumbent cow and 5 healthy cows were used as a material. Serum Mg++ (p<0.005) and Alb (p<0.05) levels were significantly decreased in the experimental groups cows compared with the control group cows. But serum CPK (p<0.005) and AST (p<0.005) levels were significantly increased in the experimental groups cows compared with the control group cows. pH (p<0.05), pC02 (p<0.05), HC03-(p<0.05) and BE (p<0.05) levels in ve-nouse blood were significantly increased in the experimental groups of cows compared with the control group of cows. But K (p<0.05) level in venouse blood was also significantly decreased in the experimental groups of cows compared with the control group of cows. As a results, decrease in magnesium level and metabolic alkalosis in the downer cow was determined. Therefore application of calcium, phosphours together with magnesium in the treatment of downer cow could be useful.